Anatomy and Secretory Structure of Leea indica (Burm.f.) Merr (Memaye) as a Typical Medicinal Plant of the Besemah Tribe for Anti-Infection and Degenerative in Lahat Regency, South Sumatra, Indonesia - Nina Tanzerina; Febrin Yohana Purba; Nita Aminasih; Endri Junaidi; Juswardi Juswardi (Green Publisher Indonesia, 2024)
Leea indica (Burm.f.) Merr, commonly known as Memaye, is a shrub utilized by the Besemah tribe in Lahat Regency, South Sumatra, for treating infectious diseases such as hepatitis and warts, as well as degenerative diseases like liver disorders. This plant's medicinal properties are primarily derived from its roots and fruits, which contain secondary metabolites like alkaloids, flavonoids, and terpenoids. Anatomical studies are crucial to identify specific structures within the plant that may store these metabolite compounds. This research aims to analyze the anatomical structure and distribution of secretory structures in the vegetative organs (leaves, stems, and roots) of Leea indica. Using a descriptive method, the study employed Paraffin and Whole mount techniques to prepare samples for microscopic observation. Results revealed the presence of epidermal tissue, basic tissue, and vascular tissue. Additionally, internal secretory structures, including cavities and two types of idioblast cells, were found to function as storage sites for secondary metabolites. These secretory structures were distributed throughout the leaves, stems, and roots of the plant.